2019
DOI: 10.18632/oncotarget.26725
|View full text |Cite
|
Sign up to set email alerts
|

AXL knockdown gene signature reveals a drug repurposing opportunity for a class of antipsychotics to reduce growth and metastasis of triple-negative breast cancer

Abstract: Triple-Negative Breast Cancer (TNBC) is an aggressive cancer subtype that is associated with a poor prognosis due to its propensity to form metastases. The receptor tyrosine kinase AXL plays a role in tumor cell dissemination and its expression in breast cancers correlates with poor patient survival. Here, we explored whether already used drugs might elicit a gene signature similar to that seen with AXL knockdown in TNBC cells and which could, therefore, offer an opportunity for drug repurposing. To this end, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 38 publications
3
31
0
Order By: Relevance
“…TFP treatment induced apoptosis of cancer cells in lots of studies (Park et al, 2016; Jiang et al, 2017; Feng et al, 2018; Goyette et al, 2019). Deregulation of cell death is involved in the pathogenesis of cancer (Qi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TFP treatment induced apoptosis of cancer cells in lots of studies (Park et al, 2016; Jiang et al, 2017; Feng et al, 2018; Goyette et al, 2019). Deregulation of cell death is involved in the pathogenesis of cancer (Qi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It could overcome EGFR inhibitor and chemotherapy resistance of lung cancer by targeting cancer stem-like cells. It also showed efficacies in suppressing metastasis in several cancers (Ashleigh et al, 2015; Feng et al, 2018; Liu et al, 2018; Goyette et al, 2019). TFP induced apoptosis of cancer cells and disrupting cell cycle progression in vitro and in vivo in numerous models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goyette et al (2019) showed that FLU affects proliferation, migration and invasion of MDA-MB-231 and Hs578T human breast cancer cells. The drug at a concentration of 20 μM reduced invasion by about 75% and 40%, while the migration was reduced to less than 0.5 and 0.4 μm/min, respectively for MDA-MB-231 and Hs578T cells.Moreover, a dose-dependent reduction in the proliferation of human breast cancer cells expressed by luciferase (MDA-MB-231-Luc) was observed.…”
mentioning
confidence: 99%
“…Indeed, a role for AXL in the progression of various breast cancer subtypes has been identified. ese include in inflammatory breast cancer [35], TNBC [64], and ER-positive [54], as well as HER2-amplified [4] breast cancers. AXL has also been implicated in more rare forms of breast tumors, including in phyllodes tumors of the breast, which are tumors that originate in stromal tissue [65], as well as in male breast cancer [66].…”
Section: The Role Of Axl In the Tumormentioning
confidence: 99%